LSM12 promotes the lung squamous cell carcinoma progression through mediating alternative splicing of ARRB1 - Lin Wu; Fangyuan Zhang; Huanhuan Chen; Gang Zhao (Communications Biology)
Abstract Like-Smith protein 12 (LSM12), an RNA-binding protein, is highly expressed in tumor tissues of patients with lung squamous cell carcinoma (LUSC). However, the role of LSM12 in LUSC is unclear. In this study, overexpression of LSM12 promotes the proliferation, migration, and invasion and prevents the apoptosis of LUSC cells. In vivo, LSM12 accelerates the tumor growth and metastasis of LUSC cells using male BALB/c nude mice. Furthermore, we find that the Sterile alpha motif domain containing 4A (SAMD4A) is directly bound to the mRNA of LSM12 and accelerates the mRNA degradation. High-throughput omics analysis is performed to identify the potential target genes of LSM12 in LUSC cells. LSM12 regulates alternative splicing events and increases exon 13 skipped splicing of ARRB1 and mRNA expression. Our findings may provide fundamental research for the investigation of the development of LUSC and the potential role of LSM12 in LUSC cells.